EFFECT OF E-GOVERNANCE POLICY ON SECURITY IN NIGERIA - Bashi B Musa; Abu Idris; Yusuf Abdulhakeem; Ndagi Salihu (Malete Journal of Accounting and Finance)
Security is a fundamental pillar for the stability and development of societies worldwide. EGovernance policy, which involves the use of digital tools and technologies in government operations, has emerged as a critical strategy for addressing modern security challenges. This study investigates the effect of E-Governance policy on security in Nigeria. The sample was drawn from 806 personnel of the Police Intelligence Department (FID), comprising the Intelligence Response Team (IRT) and Special Tactical Squad (STS) located at the force headquarters in FCT, Abuja. Multiple regression analysis and descriptive statistics were employed to achieve the study’s objectives. The major findings reveal that digital incidence reporting systems (DIRS) have a significant positive relationship with security; digital forensic tools (DFT) have a significant positive relationship with security; and CCTV surveillance systems have a significant positive relationship with security. The study concludes that if the Nigerian government focuses on providing digital incidence reporting systems, digital forensic tools, and CCTV surveillance systems, it will lead to an improved security situation in the country. It is recommended that the government at all levels allocate sufficient resources for the procurement, maintenance, and upgrade of these digital tools and systems. Additionally, the study recommends that the Nigerian government partner with international organizations and experts to provide specialized training and certification programs for Nigerian security personnel. Furthermore, the government should establish continuous monitoring and evaluation mechanisms to assess the performance and impact of digital incidence reporting systems, digital forensic tools, and CCTV surveillance.